Prevalence of chronic non-specific low back pain among caregivers of stroke survivors in Kano, Nigeria and factors associated with it: A cross-sectional study - Abdullahi, Auwal; Aliyu, Kamilu; Hassan, Auwal Bello; Sokunbi, Ganiyu Oluwaleke; Bello, Bashir; Saeys, Wim; Truijen, Steven (Frontiers in Neurology, 2022)
Purpose Low back pain (LBP) may have a specific or non-specific cause such as abnormal posture or repetitive tasks. For instance, lifting and transferring patients during caregiving for stroke survivors may predispose the caregivers to LBP. Objectives The aim of this study is to determine the prevalence of chronic non-specific LBP and factors associated with it in caregivers of stroke survivors. Method The research design used is cross-sectional study design. Participants of the study were caregivers of stroke survivors in Kano, Nigeria who were at least 18 years old. They were included if they had at least one-month experience with caregiving for at least 1 h per day. Presence of LBP and level of disability were assessed using participants' self-report and Rolland Morris Low Back Pain Disability Questionnaire respectively. The data collected was analyzed using descriptive, Chi-square statistics and Binary Logistics Regression. Result Three hundred caregivers with mean age, 33.24 ± 10.32 years in which 207 and 93 were males and females respectively, participated in the study. The results showed that, there was a high prevalence (64.7%) of LBP among the caregivers. The prevalence was significantly associated with gender (p < 0.001), age (p = 0.029), occupation (p < 0.001) and duration of caregiving (p < 0.001) of the study participants. In addition, the result of the regression model showed that, being a female (p = 0.001), a civil servant (p = 0.031), a trader (p = 0.013), and a complete caregiver (0.001); and caregiving for a duration of 5 h or more per day (p = 0.024) are significant predictors of having LBP. Similarly, level of disability due to the presence of LBP among the study participants was significantly associated with gender (p < 0.001), occupation (p < 0.001), duration of caregiving (p = 0.025), and the nature of the caregiving (p < 0.001). Conclusion Informal caregiving for stroke survivors may result in developing chronic non-specific LBP, especially among females, Civil servants, traders, complete caregivers and those with long duration of caregiving. This can add an additional burden on the family in terms of cost of care, result in reduced quality of caregiving and cause psychological stress. Thus, it is important the health of the caregivers of stroke survivors is considered during stroke rehabilitation.